2010
DOI: 10.1634/theoncologist.2010-0293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Safety Concerns and Regulatory Changes on the Usage of Erythropoiesis-Stimulating Agents and RBC Transfusions

Abstract: Purpose. Safety concerns raised in the recent oncology trials with erythropoiesis-stimulating agents (ESAs) have led to regulatory restrictions on their use. We wished to determine the impact of these changes on the use of ESAs and RBC transfusions. Conclusions. Recent ESA safety concerns and regulatory restrictions have significantly decreased ESA use. The lack of a significant impact on transfusions may be related to a lower hemoglobin threshold used to initiate ESAs or treatment of patients less likely to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
(32 reference statements)
3
17
1
1
Order By: Relevance
“…Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results. Previous studies have reported a decrease in mean Hb levels and the proportion of patients with Hb > 10 g/dL at the time of treatment initiation, findings that are in agreement with our oncology EMR database results. However, these previous studies examined that smaller study populations and fewer tumor types had shorter follow‐up periods and generally were less geographically representative .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results. Previous studies have reported a decrease in mean Hb levels and the proportion of patients with Hb > 10 g/dL at the time of treatment initiation, findings that are in agreement with our oncology EMR database results. However, these previous studies examined that smaller study populations and fewer tumor types had shorter follow‐up periods and generally were less geographically representative .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with prior studies showing decreases in ESA use and increases in transfusion use following the ESA label change and subsequent NCD. Henry et al showed that the number of ESA administrations per patient decreased from a mean of 4.6 to 2.9 following the NCD, nearly identical to our results.…”
Section: Discussionmentioning
confidence: 95%
“…The declines in ESA use in the VA echo those found in two other cancer populations, at UCLA and affiliated community practices [14] and at the MD Anderson Comprehensive Cancer Center [11,15]. Hess and colleagues [12] found a 26% reduction in ESA use during chemotherapy among patients in 39 sites across 7 states, much smaller than the 66% (colon) and 77% (lung) drops in unadjusted prevalence of ESA use in our sample (not shown).…”
Section: Discussionsupporting
confidence: 75%
“…A few single-institution and regional studies suggest that ESA use in cancer care has declined in recent years [11][12][13][14][15], but little is known about ways in which clinical decision making has changed in response to the dissemination of study results and practice guidelines, FDA advisories, product labeling changes, and CMS reimbursement restrictions. We examined ESA treatment in cancer care in the U.S. Department of Veterans Affairs Health Care System (VA), where approximately 40,000 patients are diagnosed with cancer each year nationwide.…”
Section: Introductionmentioning
confidence: 99%
“…12 Two studies of cancer patients treated at MD Anderson Comprehensive Cancer Center reported decreases in ESA use between 2006 and 2008 of 17% to 5% and 4% to 1%. 11,13 …”
Section: Discussionmentioning
confidence: 99%